Thinking Ability and Creativity Quotient in the landscape of basic education: A contextual and demographic perspective - Weeraphol Saengpanya; Ratchaneekorn Upasen (PLoS ONE, 2026)
Thinking Ability (THI) and Creativity Quotient (CQ) equips students to navigate a complex, fast-changing world. These cognitive functions drive problem-solving, innovation, and adaptability, essential for academic and personal success. In the basic education landscape (elementary and secondary levels), schools worldwide are focusing on promoting core competencies among students. The comparison for THI and CQ based on students’ demographic characteristics is little known. This study examines the levels and demographic variations of THI and CQ among basic education students in Thailand, using a learning-sufficiency framework and key of cognitive and creative developmental theories to explain their development across diverse contexts. A multi-stage random sampling method was employed, involving a total of 1,494 students from schools across various regions. Participants completed a demographic characteristics questionnaire as well as the THI and CQ scales. The results show that the level of THI and CQ among the participants were low to moderate in total and had a statistically significant difference (p < 0.05) when compared based on the demographic characteristics. The study advances theory by providing evidence of distinct patterns across demographic groups. Key implications include adopting stage-appropriate instruction, integrating inquiry- and creativity-based pedagogies, and promoting equity-focused policies to reduce demographic disparities in cognitive and creative development. These findings provide guidance for teachers, educational psychologists, curriculum developers, school leaders, and administrators in strengthening students’ THI and CQ in accordance with their demographic characteristics.